Are improved water supply and sanitation always safe for children? Implications for attaining the MDGs in the Philippines - Joseph J. Capuno; Carlos Antonio R. Tan (University of the Philippines, School of Economics (UPSE), 2012)
In 2010, the Philippines appeared to be on track to attain by 2015 its target for Millennium Development Goals 4 (Reduce child mortality), but less so for Goal 7 (Ensure environmental sustainability). In pursuit of the latter, the government expands its provision of water and services to more households. Applying propensity score matching technique on the data from the four rounds of a nationwide survey, such interventions are found to reduce the incidence of child diarrhea, a persistent top cause of child mortality, though not always. The impact of improved sources of drinking water is 1.3% to 2.6% in 1993 and 2.9% to 4.6% in 2003, but none is found in 1998 and 2008. The impact of improved sanitation is 1.2% to 2.1% in 1993 and 3.1% to 4.7% in 2008; but none is found in 1998 and 2003. In addition to health interventions, the regular monitoring of the quality of water and sanitation at the household level is suggested to achieve Goal 4.
Keywords: I12; I18; O53; 330; Water and sanitation; child health; MDGs; Philippines; Millennium Development Goals; Wasserversorgung; Gewässerbelastung; Kanalisation; Kindersterblichkeit; Gesundheitsrisiko; Philippinen